Study on Coral Reefs Influences on Wave Runup Using LABSWETM - Zulkifli, Hafizul Fahmi (Universiti Teknologi PETRONAS, 2017)
Wave runup is one of the factor which is related to coastal erosion. As the height of wave runup increases, more area of the coastline will be exposed to erosion. Coral reef is known to be a natural protection for the coastline. This research discusses about the effect towards the wave runup when coral reef is present. The hypothesis for this study is when the height of coral increases, the height of wave runup decreases. The simulation of wave runup using numerical model, in this case LABSWETM, is carried out in order for us to predict the changes and effects which occurs to the wave runup when there is presence of coral which shall be varied by height. The simulation is compared to a similar experimental simulation which is done in the laboratory. The results show how the wave runup reacts to coral reef and also the reliability of LABSWETM in predicting the wave runup.